The Victorian marionette theatre - McCormick, John, 1938- (Studies in theatre history and culture., 2004)
In this fascinating and colorful book, researcher and performer John McCormick focuses on the marionette world of Victorian Britain between its heyday after 1860 and its waning years from 1895 to 1914. Situating the rich and diverse puppet theatre in the context of entertainment culture, he explores both the aesthetics of these dancing dolls and their sociocultural significance in their life and time.